ELECTROPHORETIC STUDY ON MUSCLE AND EYE LENS PROTEINS OF THREE SCIAENIDS
Results of the electrophorctic study on muscle and eye lens proteins of three species of scianeids viz. Johnius macrorhynus (Mohan), Johnieops wgleri (Blocker) and Otolithes cuvieri (Trewavas) is reported in the present communication. The number of protein fractions in the muscle of/, vogleri,